Highly selective luminescence sensing for the detection of nitrobenzene and Fe3+ by new Cd(ii)-based MOFs. Issue 4 (4th January 2018) - Yan, Yang-Tian; Liu, Jiao; Yang, Guo-Ping; Zhang, Fang; Fan, Ya-Ke; Zhang, Wen-Yan; Wang, Yao-Yu
Abstract : Herein, three Cd(ii )-based MOFs were assembled, and the complex3 showed a high selectivity in the detection of nitrobenzene and Fe 3+ . Abstract : Herein, three new luminescent metal–organic frameworks (MOFs), namely [Cd4 (H3 L)4 (H2 O)12 ]·2.5H2 O n (1 ), [Cd(L)]·2.5H2 O·3[H2 N(Me)2 ] n (2 ), and [Cd2 (L)(DMA)]·[H2 N(Me)2 ] n (3 ), were designed and successfully prepared via a solvothermal reaction using V-shaped rigid multicarboxylate 2, 4-di(3′, 5′-dicarboxylphenyl)benzoic acid (H5 L) and Cd(ii ) salts in various solvent systems. The structural analyses indicated that the H3 L 2− /L 5− ligands took three different coordination fashions in1–3 ; this resulted in a diversity of targeted MOFs. The solid-state luminescence properties of three MOFs were studied under ultraviolet light irradiation at ambient temperature, and3 showed a high selectivity and sensitivity for nitrobenzene and Fe 3+ because of the quenching effect. Thus, it could be a potential crystalline material for detecting these substances. The mechanisms of the quenching effect and sensing properties of3 have been discussed in detail.